Informed-Principal Problem in Mechanisms with Limited Commitment - Suehyun Kwon (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies mechanism design with limited commitment where agents have correlated persistent types over the infinite horizon. The mechanism designer now faces the informed-principal problem in addition to usual issues with i.i.d. types. The paper first shows revelation principle in this context then shows sufficient conditions for obtaining full-commitment solutions with limited commitment.
Keywords: 330; mechanism design; limited commitment; revelation principle; informed-principal problem; persistence; correlated types